Model Good Governance Pengelolaan Keuangan Kampung - Siti Rofingatun; Bill Pangayow; Rudiawie Larasati (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2022)
The Good Governance Model for border village finance is needed in the integration of policies in village financial management. The purpose of this study is to model the financial good governance of border villages of the Republic of Indonesia and Papua New Guinea and their application in four border villages. Research respondents consisted of public sector accounting experts called informants to create a model of Good Governance and respondents of village officials and the community in four villages to determine the quality of the implementation of Good Governance. The analytical tool used is the Analytic Hierarchy Process. The results showed that the use of funds in accordance with the established budget which is very important for village financial management. In addition, an explanation to the community about village finances is the next important sub factor followed by openness in the financial sector, the system and procedure.